Assessment of the sanitary status of citrus germplasm - Djelouah K.; D'Onghia A.M. (Improvement of the citrus sector by the setting up of the common conservation strategies for the free exchange of healthy citrus genetic resources, 2001)
This paper is focused on the assessment of the sanitary status of citrus germplasm. In addition to the common laboratory methods, an overview is given of the use of biological indicators, which are still compulsory in the sanitary assessment of selected germplasm and field observations, collection and storage of plant material for the success of the sanitary assays. The detection facilities and the laboratory assays for the most important citrus graft-transmissible diseases, such as serological and molecular techniques, including ELISA, DTBIA, sPAGE, Dot Blot and PCR are reviewed as well.